Infective endocarditis in the military patient. Issue 3 (4th August 2015) - Gough, Andrew; Clay, K; Williams, A; Jackson, S; Prendergast, B
Abstract : Infective endocarditis (IE) is a potentially fatal cardiac infection associated with an inhospital mortality rate of up to 22%. Fifty per cent of IE cases develop in patients with no known history of valve disease. It is therefore important to remain vigilant to the possibility of the diagnosis in patients with a febrile illness and unknown source. From a military perspective, our patients are unique due to the breadth of pathogens they are exposed to, and blood-culture-negative IE is a risk. In particular, there should be awareness of Coxiella burnetii as a possible causative pathogen. In this review we incorporate the latest consensus from systematic reviews and publications identified by a literature search through Medline. We describe the diagnosis and management of IE with particular reference to the military population.